Optimizing Car Wash Services with Web-Based Ordering System - Mattola, Andi Alvian As.; Selao, Ahmad; Masnur, Masnur; Alam, Syahirun (Universitas Pancasakti, 2025)
The car wash service industry faces various operational challenges such as long queues, difficulty in finding a reliable location, and unclear information about prices and services. This study aims to optimize car wash services through a web-based booking system. This system allows customers to book services online, choose a convenient time, and make electronic payments, which can reduce waiting times and increase convenience. The research method used is a mixed approach, with data collection through surveys, interviews, and observations at several car wash locations. The results show that the implementation of a web-based booking system improves operational efficiency and customer satisfaction, especially in terms of ease of booking, speed of service, and quality of information provided. However, there is still room for improvement in terms of the timeliness of the wash and the quality of service results. This study also identifies factors that influence customer adoption of web-based systems, such as ease of use, perceived benefits, and social influence. In conclusion, the implementation of a web-based booking system has a positive impact on the performance of the car wash service business by improving operational efficiency, customer satisfaction, and service quality.